If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 2 = -6m + -4(1 + -5m) Reorder the terms: 2 + 8m = -6m + -4(1 + -5m) 2 + 8m = -6m + (1 * -4 + -5m * -4) 2 + 8m = -6m + (-4 + 20m) Reorder the terms: 2 + 8m = -4 + -6m + 20m Combine like terms: -6m + 20m = 14m 2 + 8m = -4 + 14m Solving 2 + 8m = -4 + 14m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-14m' to each side of the equation. 2 + 8m + -14m = -4 + 14m + -14m Combine like terms: 8m + -14m = -6m 2 + -6m = -4 + 14m + -14m Combine like terms: 14m + -14m = 0 2 + -6m = -4 + 0 2 + -6m = -4 Add '-2' to each side of the equation. 2 + -2 + -6m = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -6m = -4 + -2 -6m = -4 + -2 Combine like terms: -4 + -2 = -6 -6m = -6 Divide each side by '-6'. m = 1 Simplifying m = 1
| -16-(-12)= | | 1-2/t-24/t^2=0 | | 1/8(x+3)=x+5 | | -2(4-x)=12 | | 5/8(x-4)=7/8(x+4) | | 0.3(2-4.9x)-3(0.02x-3)=0.25(3-0.2x) | | 1x+6=4 | | 4+.5x=13 | | 3.08 sqrtx+18.97=2.87sqrtz+20.08 | | 4[x-3(x-2)]+1=5 | | -3/5x=7 | | 2t-0=0 | | 2t-4=12 | | 2x-(5x+16)=3-2(3x-4) | | 4w=2w+10 | | (2x-6)-(9-3x)=20 | | (3+y)(3y+8)=0 | | (3+y)(3y+8)=8 | | 2(3b-4)=4(2b+2) | | f=9/5t+32 | | 3-(4x-5)=6x-2 | | 7y=9 | | x(15+5)+25=415 | | 32/9-x=7/24 | | 7y-6x=9 | | 12x/(-5)=9 | | -6x+7y=9 | | 7x+(x+19)=14x+(9x-15) | | s(15+5)+25=415 | | 8(x-2)=3(2x+1) | | 8-3(2+4)=24 | | 3x+x+8=2x+x+6 |